Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A = lim x → 2 2 x 2 − 5 x + 2 x 3 − 3 x − 2 = lim x → 2 ( 2 x − 1 ) ( x − 2 ) ( x − 2 ) ( x + 1 ) 2 = lim x → 2 2 x − 1 ( x + 1 ) 2 = 1 3
Chọn đáp án C
( 21 + 12 - 3 + 44 + 55) x ( 2 x 6 -4x3) = (21+12-3+44+55)x( 12-12)
=(21+12-3+44+55)x0 = 0
1 + 4 : 2 x 6 - 2 + 5 x 3 - 8
= 1 + 2 x6 - 2 + 15 - 8
= 1 + 12 - 2 + 15 - 8
= 1 + 10 + 7
= 18
1 + 4 : 2 x 6 - 2 + 5 x 3 - 8
= 1 + 2 x 6 - 2 + 15 - 8
= 1 + 12 - 2 + 15 - 8
= 13 - 2 + 15 - 8
= 11 +15 - 8
= 26 - 8
= 18
a: P(x)=4x^5-4x^5-2x^3+x^4-3x^2+4x^2+3x-5x+1
=x^4-2x^3+x^2-2x+1
Q(x)=x^7-x^7-2x^6+2x^6+2x^3-2x^4+2x^4+x^5-x^5-x+5
=2x^3-x+5
b: P(x)+Q(x)
=x^4-2x^3+x^2-2x+1+2x^3-x+5
=x^4+x^2-3x+6
P(x)-Q(x)
=x^4-2x^3+x^2-2x+1-2x^3+x-5
=x^4-4x^3+x^2-x-4
= 215 nhen bạn